To solve this, we will distribute the -4y^8 to each term inside the parentheses:
-4y^8 * 10y^10 = -40y^18
-4y^8 * -5y^6 = 20y^14
-4y^8 * 2y^3 = -8y^11
Therefore, the simplified expression is:
-40y^18 + 20y^14 - 8y^11
−4y^8(10y^10−5y^6+2y^3)
9 answers
(2y^3+10)(3y^5+4)
To simplify this expression, we will distribute each term from the first set of parentheses to each term in the second set:
(2y^3 + 10)(3y^5 + 4)
First distribute 2y^3 to each term:
2y^3 * 3y^5 = 6y^8
2y^3 * 4 = 8y^3
Next, distribute 10 to each term:
10 * 3y^5 = 30y^5
10 * 4 = 40
Combine the like terms:
6y^8 + 8y^3 + 30y^5 + 40
Therefore, the simplified expression is:
6y^8 + 30y^5 + 8y^3 + 40
(2y^3 + 10)(3y^5 + 4)
First distribute 2y^3 to each term:
2y^3 * 3y^5 = 6y^8
2y^3 * 4 = 8y^3
Next, distribute 10 to each term:
10 * 3y^5 = 30y^5
10 * 4 = 40
Combine the like terms:
6y^8 + 8y^3 + 30y^5 + 40
Therefore, the simplified expression is:
6y^8 + 30y^5 + 8y^3 + 40
(5y^3+8)(−4y^6+2)
To simplify the expression (5y^3 + 8)(-4y^6 + 2), we will distribute each term from the first set of parentheses to each term in the second set:
First, distribute 5y^3 to each term:
5y^3 * -4y^6 = -20y^9
5y^3 * 2 = 10y^3
Next, distribute 8 to each term:
8 * -4y^6 = -32y^6
8 * 2 = 16
Combine the like terms:
-20y^9 + 10y^3 - 32y^6 + 16
Therefore, the simplified expression is:
-20y^9 - 32y^6 + 10y^3 + 16
First, distribute 5y^3 to each term:
5y^3 * -4y^6 = -20y^9
5y^3 * 2 = 10y^3
Next, distribute 8 to each term:
8 * -4y^6 = -32y^6
8 * 2 = 16
Combine the like terms:
-20y^9 + 10y^3 - 32y^6 + 16
Therefore, the simplified expression is:
-20y^9 - 32y^6 + 10y^3 + 16
(−6y+7)(5y+5)
To simplify the expression (-6y + 7)(5y + 5), we will distribute each term from the first set of parentheses to each term in the second set:
First distribute -6y to each term:
-6y * 5y = -30y^2
-6y * 5 = -30y
Next, distribute 7 to each term:
7 * 5y = 35y
7 * 5 = 35
Combine the like terms:
-30y^2 - 30y + 35y + 35
Simplify by combining like terms further:
-30y^2 + 5y + 35
Therefore, the simplified expression is:
-30y^2 + 5y + 35
First distribute -6y to each term:
-6y * 5y = -30y^2
-6y * 5 = -30y
Next, distribute 7 to each term:
7 * 5y = 35y
7 * 5 = 35
Combine the like terms:
-30y^2 - 30y + 35y + 35
Simplify by combining like terms further:
-30y^2 + 5y + 35
Therefore, the simplified expression is:
-30y^2 + 5y + 35
(3y+4)(4y+5)
To simplify the expression (3y + 4)(4y + 5), we will distribute each term from the first set of parentheses to each term in the second set:
First distribute 3y to each term:
3y * 4y = 12y^2
3y * 5 = 15y
Next, distribute 4 to each term:
4 * 4y = 16y
4 * 5 = 20
Combine the like terms:
12y^2 + 15y + 16y + 20
Simplify by combining like terms further:
12y^2 + 31y + 20
Therefore, the simplified expression is:
12y^2 + 31y + 20
First distribute 3y to each term:
3y * 4y = 12y^2
3y * 5 = 15y
Next, distribute 4 to each term:
4 * 4y = 16y
4 * 5 = 20
Combine the like terms:
12y^2 + 15y + 16y + 20
Simplify by combining like terms further:
12y^2 + 31y + 20
Therefore, the simplified expression is:
12y^2 + 31y + 20